Degree in Rural Education: Intentions in the Training of Field Educators in Marajó - Miranda Costa, Eliane (2017)
The text is the result of the master survey conducted in the city of Portel, in thearchipelago of Marajó. It ims to discuss the intentions of forming educators ofthe field from the Bachelor,s Degree in Rural Education. Methodologically it is acase study of one type of qualitative approach, which collected the data using thefollowing techniques: semi-structured interviews, non-participant observation,closed questionnaire and document analysis. The data analyzed in the light ofthe content analysis technique in dialogue with theorists, like Arroyo (2011),Caldart (2010), Molina (2010) and others, made it possible to consider that oneof the forming intentions is the conquest of new schools not in the sense of a newphysical structure, but an open space for dialogue and debate.